2006
DOI: 10.1111/j.1439-0523.2006.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of seed storability in rice

Abstract: A double haploid population, which consists of 127 lines derived from anther culture of a typical indica and japonica hybrid ÔZYQ8Õ/ÔJX17Õ, was used in this study. Seed storability was investigated by using the storage property measured by the difference of seed germination rates before and after treatment of the rice seeds under 40°C and 95% relative humidity for 10 days in a phytotron. Three QTLs related to rice seed storability were detected on chromosomes 9, 11 and 12, with the LOD scores 2.76, 4.83 and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 15 publications
1
40
0
Order By: Relevance
“…Unexpectedly, the allele originating from Milyang 23 in the locus of qMT-SGC1.1 decreased seed germination capability, whereas all other alleles from Milyang 23 in the other loci of the QTLs increased seed germination capability. It was revealed that seed germination capability exhibited different expression patterns between different rice varieties, which was consistent with the findings of previous studies (Kameswara and Jackson, 1996;1997;Zeng et al, 2006). In DT-RILs, we identified two novel QTLs (qDT-SGC2.1 and qDT-SGC3.1) for seed germination capability, which increased the seed germination capability in Dasanbyeo alleles.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Unexpectedly, the allele originating from Milyang 23 in the locus of qMT-SGC1.1 decreased seed germination capability, whereas all other alleles from Milyang 23 in the other loci of the QTLs increased seed germination capability. It was revealed that seed germination capability exhibited different expression patterns between different rice varieties, which was consistent with the findings of previous studies (Kameswara and Jackson, 1996;1997;Zeng et al, 2006). In DT-RILs, we identified two novel QTLs (qDT-SGC2.1 and qDT-SGC3.1) for seed germination capability, which increased the seed germination capability in Dasanbyeo alleles.…”
Section: Discussionsupporting
confidence: 90%
“…To date, some quantitative genetic studies have been conducted to detect QTLs for analysis of seed germination capability (Miura et al, 2002;Sasaki et al, 2005;Xue et al, 2008;Zeng et al, 2006). Among these QTL analyses, the QTL on chromosome 9 was consistently identified in three independent studies (Miura et al, 2002;Sasaki et al, 2005;Xue et al, 2008), and subsequently, the effect of this QTL was confirmed with chromosome segment substitution lines (CSSLs) by Shigemune et al (2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we compared the longevity QTL regions detected here with those described in rice (Miura et al 2002;Zeng et al 2006) by using the colinearity information of Stein et al (2007). For two of the barley QTLs co-linearity to loci in rice may be suggested.…”
Section: Discussionmentioning
confidence: 94%
“…In total four QTLs located on chromosomes 1 (two closely linked QTLs), 3 and 5 were identified. Other studies were performed in rice, where chromosomes 2, 4, 9 (two QTLs) 11 and 12 carry QTLs for seed longevity (Miura et al 2002;Zeng et al 2006;Shigemune et al 2008). In the present study three barley mapping populations were analysed in parallel and four genomic regions associated with seed longevity QTLs were identified on chromosomes 2HL (QLng.ipk-2H), 5HL (QLng.ipk-5H.1, QLng.ipk-5H.2) and 7HL (QLng.ipk-7H).…”
Section: Discussionmentioning
confidence: 99%